DCC: a Swiss army knife for structure factor analysis and validation. Issue 3 (18th April 2016) - Yang, Huanwang; Peisach, Ezra; Westbrook, John D.; Young, Jasmine; Berman, Helen M.; Burley, Stephen K.
Abstract : DCC is a wrapper for third‐party software packages to aid in structure factor analysis and validation. As the results are recorded in PDBx/mmCIF format, the output from DCC can be used in automatic data pipelines. Abstract : Since 2008, X‐ray structure depositions to the Protein Data Bank archive (PDB) have required submission of experimental data in the form of structure factor files. RCSB PDB has developed the program DCC to allow worldwide PDB (wwPDB;http://wwpdb.org ) biocurators, using a single command‐line program, to invoke a number of third‐party software packages to compare the model file with the experimental data. DCC functionality includes structure factor validation, electron‐density map generation and slicing, local electron‐density analysis, and residual B factor analysis. DCC outputs a summary containing various crystallographic statistics in PDBx/mmCIF format for use in automatic data processing and archiving pipelines.